2022
DOI: 10.3390/biomedicines10112975
|View full text |Cite
|
Sign up to set email alerts
|

The TRACK-MS Test Battery: A Very Brief Tool to Track Multiple Sclerosis-Related Cognitive Impairment

Abstract: Tracking cognition in patients with multiple sclerosis (MS) is important for detection of disease progression but it is often not performed in routine settings due to time constraints. This exploratory cohort study aims to develop a very brief repeatable tracking tool with comparable test quality criteria to the current gold standard, the Brief International Cognitive Assessment for MS (BICAMS). The study included 88 participants (22 healthy controls, 66 MS patients) who were examined at baseline and at one-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…The studies presented provide valuable insights into the complex relationship between drug abuse, BP, dysmenorrhea, WML, FD, and SCZ. These findings contribute to our understanding of the structural and functional organization of the brain in neuropsychiatric disorders and offer potential biomarkers for early detection and personalized treatment approaches (42)(43)(44)(45). Additionally, the use of machine learning to identify brain structure patterns associated with symptoms and impairments could lead to more targeted interventions for individuals with psychiatric disorders (46-48).…”
mentioning
confidence: 92%
“…The studies presented provide valuable insights into the complex relationship between drug abuse, BP, dysmenorrhea, WML, FD, and SCZ. These findings contribute to our understanding of the structural and functional organization of the brain in neuropsychiatric disorders and offer potential biomarkers for early detection and personalized treatment approaches (42)(43)(44)(45). Additionally, the use of machine learning to identify brain structure patterns associated with symptoms and impairments could lead to more targeted interventions for individuals with psychiatric disorders (46-48).…”
mentioning
confidence: 92%
“…The prevalence of cognitive impairment in patients with MS varies by age and may be difficult to distinguish from other causes (e.g., AD) in older patients (Luczynski et al, 2019;Benedict et al, 2020). A cohort study testing MS-related cognitive impairment found greater differences between MS patients (n = 66) and healthy controls (n = 22) (Taranu et al, 2022). Although the exact pathogenesis of MS with cognitive impairment is still unclear, it is thought to be primarily related to pathological changes in lesioned and normal-appearing white matter, specific neural gray matter structures, and immunological changes, especially to synaptic transmission and plasticity impact (Portaccio and Amato, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Another study of performance on tests from the Brief International Cognitive Assessment for MS (BICAMS), 6 the current gold standard brief cognitive battery for MS that includes the SDMT, found improvements at the 1-year follow-up on all cognitive test measures. 7 Failure to detect cognitive decline is not restricted to studies with short follow-up periods or patients early in disease course. A 2021 study of BICAMS in an Irish cohort with average disease duration of 10 years at baseline found no significant differences in SDMT and significant improvements in both CVLT-II and BVMT-R ( p ’s = 0.004 and 0.001, respectively) at the 5-year follow-up.…”
mentioning
confidence: 99%